Classical paintings may trigger pain and pleasure in the gendered brain. (December 2018) - de Gelder, Beatrice; Watson, Rebecca; Zhan, Minye; Diano, Matteo; Tamietto, Marco; Vaessen, Maarten J.
Abstract: The human body is the most common object of pictorial representation in western art and its representations trigger a vast range of experiences from pain to pleasure. The goal of this study was to investigate brain activity triggered by paintings of male and female body images exemplifying conditions associated with pleasure or pain. Our findings show participant-general as well as gender specific brain activity for either the pain or the pleasure conditions. Although our participants were fully aware that they were viewing artworks, the inferior parietal lobule – known for its role in the perception of emotional body images – and the somatosensory cortex related to touch were selectively active for female body paintings in all participants in the pleasure conditions. As regards gender we observed that the sight of female bodies activated the subgenual anterior cingulate cortex in males, an area known to subserve autonomic arousal. In contrast, in females the sight of the male body activated reward and control related parts of the dorsal anterior cingulate cortex. This study supports the notion that some basic evolutionary processes operate when we view body images, also when they are cultural heritage paintings far removed from daily experience.